Influence of perceptions and stereotypes of the nursing role on career choice in secondary students: A regional perspective. (March 2018) - Raymond, Anita; James, Ainsley; Jacob, Elisabeth; Lyons, Judith
Abstract: Background: This study examined the influence that perceptions and stereotypes of the nursing role had on future career choice of rural secondary students. Objective: The study was undertaken to identify a method of attracting final year secondary school students to an undergraduate nursing degree at a rural University. Design: A mixed method study using a pre–post-interventional design. Setting: The rural campus of an Australian university. Participants: 71 secondary students attending a secondary school career development program at a rural Australian university. Method: Semi structured questionnaires were used for data collection. The surveys were analysed using descriptive statistics and content analysis of open-ended survey questions. Results: The research supports the importance of being aware of young people's impressions about nurses and nursing as a career, to ensure the successful implementation of targeted recruitment. Conclusion: Targeted recruitment strategies can increase students' awareness of the wide variety of pathways within nursing, rather than leaving awareness to what family, friends or career advisers tell them, or how nurses are portrayed on television, movies and the media. Highlights: Understanding young people's impressions regarding nursing as a career is important. Awareness of different nursing roles and career pathways results in increased consideration of nursing as a prospective career. Targeted recruitment can aid in assisting students choose nursing as a career.